Web design: a conceptual reflection - Santos, Elsa (2018)
This article presents a proposal of featuring all the Web Designer activity in Web Engineering context, based in a recent experience from a great enterprise connected to Web Information Systems. More specifically, is a re-invention of the Web Design, about the concept of Web Designer roles and tools, the integration and the role of a Web Designer in developing Web Software. Once the role of a Web Designer is very important in the initial phase of developing Web Software, especially completing the requirements, it was produced a quiz to support the activity of the requirements audit, to make the client audit phases more beneficial. This article is fulfill reflects a reflection about the Web Marketing reality, once it determines the success of a website.